FAKTOR-FAKTOR YANG DIPERTIMBANGKAN DALAM MEMILIH PROFESI AKUNTAN PUBLIK: SUATU ANALISIS KOMPARATIF MINAT MAHASISWA AKUNTANSI BERDASARKAN WILAYAH - Munawaroh, Munawaroh SE., Ak., MM., CA., CSRS. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study’s purpose was to analyze the comparation of Region, Income, Professional Training, Social Values, Work Environment and Job Market Consideration on the Accounting student’s interest choose the Public Accountant Profession. Using 100 samples and paired T-test shows that Professional Training and Job Market Considerations are as the difference factors on the Accounting student’s VII semester interest choose the Public Accountant Profession